2015
DOI: 10.1097/hjh.0000000000000712
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed and uncontrolled hypertension among the adults in rural Bangladesh

Abstract: High prevalence of undiagnosed hypertension, and more than 50% of the treated hypertension being uncontrolled puts a great challenge ahead for Bangladesh, a resource-poor setting. Regular health check or health screening along with implementation of hypertensive guidelines should be reinforced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 37 publications
5
24
0
3
Order By: Relevance
“…High BMI is an established risk factor for hypertension15; several studies found that overweight/obesity had the strongest association with hypertension 35 38 39. Body weight is the balance between consumption and expenditure of energy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High BMI is an established risk factor for hypertension15; several studies found that overweight/obesity had the strongest association with hypertension 35 38 39. Body weight is the balance between consumption and expenditure of energy.…”
Section: Discussionmentioning
confidence: 99%
“…Bangladesh, like many other LMICs, is undergoing an epidemiological transition and an increased understanding of the burden and risk factors of hypertension is necessary to combat the increasing burden 13. A nationally representative survey conducted in 2011 (Bangladesh Demographic and Health Survey 2011 (BDHS-2011)) suggests that the prevalence of hypertension including undiagnosed and uncontrolled hypertension in Bangladeshi adults is high 14–18. However, the available data are not adequate to provide regional-level or district-level estimates.…”
Section: Introductionmentioning
confidence: 99%
“… 17 Likewise, we did not find any statistically significant association between smoking status and HTN diagnosis, contrary to the results reported by other authors. 18 …”
Section: Discussionmentioning
confidence: 99%
“…These findings are not surprising as undiagnosed disease is also common in the general population. About half of the persons living with diabetes mellitus globally are undiagnosed [ 29 ], and surveys in Africa and Asia have found a high prevalence of undiagnosed hypertension [ 30 , 31 , 32 ]. Similarly, in the few studies that have prospectively measured blood pressure in people living with HIV, hypertension was newly diagnosed in 20–45% of cases [ 10 , 11 , 14 ].…”
Section: Discussionmentioning
confidence: 99%